Module-Based Training for Teacher Professional Development in Madrasah - Ridhwan Latuapo (Jurnal Pendidikan Islam, 2023)
In the era of Industry 4.0, teachers are expected to exhibit a professional attitude in fulfilling their educational responsibilities. Despite their involvement in numerous activities, the level of professionalism among teachers has not seen significant growth. This research aims to analyze the effectiveness of using the SKI (Sejarah Kebudayaan Islam/Islamic Culture and History) Module in enhancing the professionalism of SKI teachers. The study was conducted in a madrasah affiliated with the Ministry of Religion in the Maluku Province. A total of 20 SKI teachers from the madrasah in Ambon City and Central Maluku Regency were selected as research participants. The research utilized a quantitative-qualitative approach, collecting data through observations, interviews, and product assessments. The results indicated that the module's validity score was 90.38, indicating high validity. The product rating was 3.563.56, demonstrating a very high level of quality. Additionally, the assessment of learning tool preparation scored 7.84, representing a high level of proficiency. The mastery of learning material achieved a score of 82.04, signifying a very high level of competence. The preparation of research proposals scored 69.269.2, indicating a medium level of readiness. Overall, the findings suggest that training using modules can effectively enhance the professionalism of SKI teachers within the Ministry of Religion in the Maluku Province.